Work Engagement, Dan Beban Kerja Memiliki Pengaruh Terhadap Komunikasi Teraupetik Bidan - Yane, Novi (Jurnal Penelitian Kesehatan SUARA FORIKES, 2022)
The existence of a hospital requires the value of existence of its existence, this will involve many aspects including the quality of service Basically, the hospital must continue to provide the best service. The quality of hospital services are influenced by several factors, including the most dominant is human resources. Midwives as human resources in directly interacting with the community have an important role in carrying out services in hospitals. One of the factors in improving services is the presence of therapeutic communication. The purpose of this study was to determine and analyze the effect of work engagement and workload on therapeutic communication at Torabelo Sigi Hospital. The number of samples taken was 105 respondents from a total population of 116 respondents The sampling technique is simple random sampling. The method carried out is by cross sectional study . The instruments used are questionnaires and statistical techniques used linear regression analysis. The results of the study proved that there is an influence of high work engagement on the effectiveness of therapeutic communication and low workload has a positive impact on therapeutic communication. The involvement of work has a very impact on therapeutic communication  that it increases public trust in The Torabelo Sigi Regional Hospital and by managing the workload to be optimal is very necessary to be able to increase the effectiveness of therapeutic communication that has been carried out